Lysobacter enzymogenes prevents Phytophthora infection by inhibiting pathogen growth and eliciting plant immune responses - Lin, Long; Yang, Zixiang; Tao, Min; Shen, Danyu; Cui, Chuanbin; Wang, Pingping; Wang, Limin; Jing, Maofeng; Qian, Guoliang; Shao, Xiaolong (Frontiers in Plant Science, 2023)
The Phytophthora pathogen causes enormous damage to important agricultural plants. This group of filamentous pathogens is phylogenetically distant from fungi, making them difficult to control by most chemical fungicides. Lysobacter enzymogenes OH11 (OH11) is a biocontrol bacterium that secretes HSAF (Heat-Stable Antifungal Factor) as a broad-spectrum antifungal weapon. Here, we showed that OH11 could also control a variety of plant Phytophthora diseases caused by three major oomycetes (P. sojae, P. capsici and P. infestans). We provided abundant evidence to prove that OH11 protected host plants from infection by the Phytophthora pathogen by inhibiting mycelial growth, digesting cysts, suppressing cyst germination, and eliciting plant immune responses. Interestingly, the first two processes required the presence of HSAF, while the latter two did not. This suggested that L. enzymogenes could prevent Phytophthora infection via multiple previously unknown mechanisms. Therefore, this study showed that L. enzymogenes could serve as a promising alternative resource for controlling multiple Phytophthora diseases.